Cadaveric Donation and Post-mortem Reuse of Pacemakers and Defibrillators in Nepal: Medical, Legal and Ethical Challenges - Sedhai, Yub Raj; Ochasi, Aloysius; Basnyat, Soney; Acharya, Deepak; Clark, Peter (Journal of Advances in Internal Medicine, 2017)
Cardiovascular diseases (CVDs) are the number one cause of death globally. An estimated 17.5 million people died from CVDs in 2012, representing 31% of all global deaths. Over three quarters of all deaths related CVDs take place in low- and middle-income countries (LMICs). Studies have estimated that 1 to 2 million people worldwide die each year due to lack of access to cardiac rhythm management devices (CRMDs) i.e. implantable cardiac defibrillator (ICD) or a pacemaker. The principal challenge is the high cost of these devices and the resource constraint in LMICs. A growing body of literature, mostly single center, uncontrolled and retrospective studies has suggested reuse of CRMDs from deceased donors as a safe and effective alternative. This paper seeks to propose the concept of post-mortem CRMD donation and reutilization program within Nepal as a life-saving initiative. Though the spirit of the program is in line with the ethical principles of respect for persons, beneficence, justice, and the common good, it is challenged with several logistical barriers and legal concerns. In this paper we have discussed the clinical, legal and ethical perspectives with a literature review on similar programs.